Pengaruh penyuluhan 3M terhadap kepatuhan pelaksanaan pemberantasan jentik nyamuk di Desa Tolong Kabupaten Pulau Taliabu - Sutjiato, Margareth (UNIVERSITAS SAM RATULANGI, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a disease that is difficult to cure, this is because until now there has not been found a drug or vaccine to control DHF. DHF is transmitted through the Aedes aegypti mosquito which contains the dengue virus. The Aedes aegypti mosquito only lives at temperatures between 80C–37°C. There are various breeding-places for mosquitoes, for example those found in bathtubs, jars/storage places for drinking water, empty cans, plastic drinking water, used tires and other artificial containers.Aim: To determine the effect of 3M Counseling on Compliance with the Implementation of Mosquito Larva Eradication in Help Village, Taliabu Island Regency.Methods: This type of research uses quantitative methods with a quasi-experimental approach. The sample in this study uses purposive sampling technique, the number of samples is 83 respondents.Results: Based on the results of statistical tests using paired t test, the value of ρ-value = 0.000 is smaller than the value of α = 0.05, meaning that H0 is rejected, then 3M counseling affects the compliance of mosquito larvae eradication implementation in Tolong Village, Taliabu Island Regency.Conclusion: This study concludes that adherence to the implementation of mosquito larvae before 3M counseling in the village of Help, Taliabu Island Regency. The results of non-adherence were 45 respondents (54.2%) and before 27 respondents (32.5%). This research can be used as one of the data in conducting counseling interventions to reduce dengue fever.Keywords: DHF, 3M, Compliance with mosquito larvae eradication